Development of a wireless current controlled stimulator for individuals with spinal cord injury - Masdar, Aizan (2016)
A spinal cord injury (SCI) has a severe impact on human life in general as well as on the physical status and condition. The use of electrical signals to restore the function of paralyzed muscles is called functional electrical stimulation (FES). FES is a promising way to restore mobility to SCI by applying low level electrical current to the paralyzed muscles so as to enhance that person’s ability to function and live independently. However, due to the limited number of commercially available FES assisted exerciser systems and their rather high cost, the conventional devices are unaffordable for most peoples. Thus , this project is concerned with the development of low cost current controlled stimulator mainly for the paraplegic subje cts. The developed device is based on a microcontroller, wireless based system using Zigbee module, voltage to current converter circu it and should produce accurate monopolar and bipolar current pulses, pulse trains, arbitrary current waveforms, and a trigger output for FES applications. A simple low cost current adjustable circuit for electrical stimulator was designed and developed who se output consists of current pulses with a wide range of rectangular waveforms (monophasic/biphasic), ranging from 10 120mA with a step of 2mA and a time resolution of 10μs. The circuit also capable of adjusting the current amplitude, frequency and pulse width of the output signals. The advantages of the device are the high level of output current amplitude controlled by low level of control voltage, the capability of fine time and amplitude tuning, the vast range of output waveforms, wireless ba sed system using zigbee module and the use of low cost electronics components in its structure which make it economically efficient for being used in vario us FES research studies as well